ChurchInAction: the role of religious interventions in times of COVID-19 - Del Castillo, Fides A. (Animo Repository, 2020)
In a recently published letter to the editor of this journal, the authors have called for the need to establish psychological support structures that cater to people's mental health in this time of the coronavirus disease 2019 pandemic. To be more holistic, we extend this call to include people's spiritual well-being as well. We highlight the initiatives of the Philippines' religious sector. In particular, we report some of the interventions made by the Roman Catholic Church that have led to the social media hashtag, #ChurchInAction. These religious and spiritual interventions showcase the efforts of the Philippine Church and play an important role in providing assistance in time of public health crisis. © Crown copyright 2020.